The Relationship Between Family Support and Patient Adherence to Hypertension Medication Therapy at the Sukabumi Buay Bahuga Community Health Center - Sulistiyani; Agata, Annisa; Nurwinda Sari, Nova (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Family support plays a crucial role in the hypertension treatment process, ensuring optimal care (Prihatin et al., 2020). This support ensures that elderly individuals receive more attention and supervision, thereby minimizing complications. The purpose of this study was to determine the relationship between family support and patient adherence to hypertension medication therapy at the Sukabumi Buay Bahuga Community Health Center in 2024. This quantitative study used an analytical survey design with a cross-sectional approach. The population of this study was 206, resulting in a sample size of 135 individuals. Purposive sampling was used as the sampling technique. Univariate analysis revealed that the majority of respondents (50 respondents (37.0%) had low medication adherence, and 62 respondents (45.9%) received insufficient family support. Based on the statistical test results, a p-value of 0.845 was obtained, or p-value > 0.05, indicating that Ho is not accepted. This means there is no relationship between family support and medication adherence in hypertension patients at the Sukabumi Buay Bahuga Community Health Center. This study can help identify the family support needs of hypertension patients to improve their medication adherence. This can provide valuable insights for healthcare professionals in designing more effective interventions.